Supervision Strategies for Improving Community Welfare Program in East Indonesia Area - Herlina Sakawati; Sulmiah Sulmiah; Novayanti Sopia Rukmana; Widyawati Widyawati (Indonesian Association for Public Administration (IAPA), 2020)
Various programs to improve community welfare established by the government exist as an effort to solve the problem of poverty, the implementation of which must be accompanied by effective supervision so that the objectives of the program can be achieved. This article aims to explain the monitoring strategy for the implementation of programs to improve community welfare, by selecting the people's salt business program in the Eastern Indonesia region as a case study. The qualitative research method was carried out through interviews and observations, which were then strengthened by secondary data on the strategy of monitoring the people's salt business program. The findings in the field show that the implementation of supervision of the people's salt business program can run optimally, if the stakeholders involved in the supervisory task continue to coordinate well, carry out supervision according to a predetermined time, form a Coordination and Coordination Team in accordance with the direction of the Minister of Marine Affairs and Fishery. In addition, it is necessary to increase the number of employees, as well as to guarantee employee safety while carrying out supervisory duties.